Implications of Lifestyle Hedonism on Psychology Well-Being - Siti Eni Aisyah Simbolon (Business Finance Analyst Co., 2023)
The flow of globalization and technological sophistication have an impact on changes in people's lifestyles. The hedonistic lifestyle has become a lifestyle that is loved by the community. The lifestyle that aims to achieve this pleasure makes hedonism have implications for the psychology of individual well-being. This article aims to describe the implications of a hedonistic lifestyle on the psychology well-being. This paper uses a qualitative approach with a literature study method. The results showed that the hedonistic lifestyle was not able to achieve good psychological well-being in individuals. Furthermore, this hedonism is also able to fade morals, morals and human nature.